2011
DOI: 10.1017/s0954394511000159
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and social forces in dialect shift: Gradual change in London Asian speech

Abstract: A B S T R A C TThis study examines the retention of a non-native dialect feature by British Asians in London. We examine the use of one Punjabi feature (t-retroflexion) and one British feature (t-glottaling) across three groups: first-generation non-native immigrants and two age groups of second-generation British Asians. Cognitively oriented models predict that non-native features will either be innately blocked (Chambers, 2002) or reallocated by native generations. A socially oriented model allows for more g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 45 publications
5
90
0
Order By: Relevance
“…This influence may be present in bilingual settings or in situations where language shift has already taken place as a SUBSTRATE. Such substrate effects are noted in many established global varieties of English (Schneider, 2011, p.201 see also Sankoff, 2001 for a review) and in the contemporary speech of monolingual descendants of immigrant communities (e.g. Holmes, 1996;Fought, 1999;Sharma & Sankaran, 2011;Kirkham, 2013). The presence of a Welsh substrate effect on varieties of Welsh English is well attested, both at the level of phonology (Wells, 1982, p. 377; Thomas, 1997, p. 67;Penhallurick, 2004) and morphosyntax (e.g.…”
Section: Long-term Language Contactmentioning
confidence: 95%
“…This influence may be present in bilingual settings or in situations where language shift has already taken place as a SUBSTRATE. Such substrate effects are noted in many established global varieties of English (Schneider, 2011, p.201 see also Sankoff, 2001 for a review) and in the contemporary speech of monolingual descendants of immigrant communities (e.g. Holmes, 1996;Fought, 1999;Sharma & Sankaran, 2011;Kirkham, 2013). The presence of a Welsh substrate effect on varieties of Welsh English is well attested, both at the level of phonology (Wells, 1982, p. 377; Thomas, 1997, p. 67;Penhallurick, 2004) and morphosyntax (e.g.…”
Section: Long-term Language Contactmentioning
confidence: 95%
“…On the other hand, in contrast to the latter, they commonly realised Sylheti coronals as alveolars, and produced some tokens of /gʱ/ as [g]. Differences of this kind between first-generation migrants and second-generation heritage language users are well attested (e.g., Evans et al, 2007;McCarthy et al, 2011McCarthy et al, , 2013Nagy & Kochetov, 2013;Sharma & Sankaran, 2011), and have been explained in a number of ways. Chambers (2002) claimed that second-generation speakers have an innate accent filter that blocks non-native features in the host language.…”
Section: Acquisition Patterns: Adultsmentioning
confidence: 99%
“…Kirkham (2011), for example, argued that British Asians from Sheffield used retroflex realisations of English /t/ to signal their Asian identity, rather than inadvertently as a result of cross-linguistic interactions, since the use of these forms could not be predicted on the basis of their language use patterns, with even monolingual English speakers from the community using them. Sharma & Sankaran (2011), in turn, examined the acquisition of a native feature, /t/ glottaling, and a non-native feature, /t/ retroflexion, in British Asians from London. They found that younger second-generation speakers used /t/ retroflexion in English to signal their Asian identity, while older second-generation speakers followed first-generation speakers' non-native use of /t/ retroflexion, but unlike them, used /t/ glottaling natively.…”
Section: Introductionmentioning
confidence: 99%
“…Class and ethnicity are particularly interesting in this regard, as different generations may have substantially different experiences of racialised class structures (Platt 2005), which can impact upon how they use linguistic variation for identity work (e.g. Sharma & Sankaran 2011). It is therefore imperative to consider the ways in which ethnicity itself is structured as a class relation (Rampton 2010:2).…”
mentioning
confidence: 99%